Intersubject and intrasubject variability of gastric volumes in response to isocaloric liquid meals in functional dyspepsia and health - Fruehauf, H; Goetze, O; Steingoetter, A; Kwiatek, M; Boesiger, P; Thumshirn, M; Schwizer, W; Fried, M (Neurogastroenterology and motility, 2007)
Gastric emptying (GE) has a considerable variability, but data on reproducibility of gastric volume measurements are sparse. We aimed to study the reproducibility of postprandial gastric volume responses and GE using magnetic resonance imaging (MRI) in healthy controls (HC) and patients with functional dyspepsia (FD). Eight HC and eight FD patients underwent a MRI study on two occasions. MR images were acquired in seated position before and up to 120 min after liquid meal administration (200 mL, 300 kcal). Fasting (V0), initial postprandial stomach volumes (V1), volume changes (V1 - V0) and meal emptying half-times (T 1/2) were determined. Intersubject and intrasubject coefficients of variation (CV(inter), CV(intra)) and Pearson's correlation coefficients (r) were calculated. T 1/2 on both occasions were (mean +/- SD) 113 +/- 28 and 121 +/- 30 min in HC (ns) and 127 +/- 31 and 128 +/- 37 min in FD (ns), respectively. In HC, CV(inter), CV(intra), r were 31%, 23%, 0.49 for V0; 13%, 7%, 0.68 for V1; 10%, 4%, 0.71 for V1 - V0 and 25%, 7%, 0.90 for T 1/2. In FD these parameters were for V0: 42%, 41%, -0.06; for V1: 18%, 10%, 0.40; for V1 - V0: 20%, 14%, 0.74 and for T 1/2: 26%, 10%, 0.84. The stomach accommodates to a given meal volume, resulting in similar and reproducible postprandial volumes within- and between-subjects. MRI provides reproducible measurements of gastric volume responses in health and disease.